Photorefractive and pyroelectric photonic memory and long-term stability in thin-film lithium niobate microresonators - Xinyi Ren; Chun-Ho Lee; Kaiwen Xue; Shaoyuan Ou; Yue Yu; Zaijun Chen; Mengjie Yu (npj Nanophotonics)
Abstract The stability of integrated photonic circuits is crucial for applications requiring high frequency precision or robust operation over time, such as optomechanical sensing, frequency conversion, optical communication, and quantum optics. Photonic memory is useful for low-energy optical computing and interconnects. Thin-film lithium niobate (TFLN), an emerging photonic platform, exhibits complex material properties including pyroelectric and photorefractive effects which could cause intra-device drift and excess noise under different conditions and enable photonic memory. However, the long-term stability and memory effect of these properties remain unexplored. Herein, we discovered a long-lived refractive index change in Z-cut TFLN microresonators induced by light excitation and temperature variation, with recovery times exceeding 10 h. This instability strongly depends on thin film’s crystal orientations. Leveraging the long-term photonic memory, we realize optical trimming of cavity resonance frequencies. Our result offers insights towards understanding the fundamental noise properties and dynamic behavior of integrated TFLN material and devices.